GE_GERICHTE P/6529/2024 vom 22. Januar 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;ADMINISTRATION DES PREUVES;ASSISTANCE JUDICIAIRE | CPP.310.al1.leta; CPP.147.al1; CP.307; CP.251; CPP.136